Influence of Family Integrated Care on the Intestinal Microbiome of Preterm Infants With Necrotizing Enterocolitis and Enterostomy: A Preliminary Study - Yang, Mengyang; Du, Juan; Yang, Qin; Dou, Wenyan; Jiang, Min; Hei, Mingyan (Frontiers in Pediatrics, 2021)
The aim of this study was to investigate the influence of family integrated care (FICare) on the intestinal microbiome of preterm infants with necrotizing enterocolitis and enterostomy. This was a prospective pilot study at Beijing Children’s Hospital. Premature infants with an enterostomy who met the enrollment criteria were divided into the 2-week FICare and non-FICare groups(non-randomly). We collected their fecal samples and subjected the intestinal microbiomes to 16S rRNA gene sequencing. Operational taxonomic units (OTU) were analyzed to assess the intestinal microbiome richness, and we then carried out α-diversity, β-diversity, and species clustering analyses and a linear discriminant analysis (LDA) effect size (LEfSe) analysis to identify the differences in the microbial communities between the two groups. There were 12 patients enrolled in the study (FICare, n=7; non-FICare, n=5). There were no significant between-group differences in demographic characteristics, or in the relative abundances of phyla and genera. The major bacterial phyla were Proteobacteria, Firmicutes, and Actinobacteria, and Serratia, Enterococcus, Cronobacter, and Bifidobacterium dominated at the genus level. The α-diversity analysis indicated that the intestinal flora was more diverse in the non-FICare group than the FICare group (p<0.05). However, most of the other indicators did not suggest a difference between the two groups. There was a high proportion of shared OTUs between the two groups, and the PCoA and clustering analyses indicated that the two groups were difficult to distinguish, indicating that the intestinal microbiomes were relatively similar between the groups. In summary, short-term FICare did not show significant positive effect on the establishment of intestinal flora diversity in premature infants with necrotizing enterocolitis and enterostomy. However, it is difficult to make a conclusion from a trial with such a small sample size. Further study is required. The trial was registered in the Chinese Clinical Trial Registry (ChiCTR⁃OPN⁃17011801).